ANALISIS PERFORMANSI IMPLEMENTASI COMBAT DI SPV PURWAKARTA - Rofiq, M. Ainur (Jurnal Teknik Elektro, 2004)
One of way to solve coverage problem for the time being is place a combat as new site.Before and after implemented, Compact Mobile Base Station (Combat) need to analyzeperformance using simulation software and the the reality of data in the field. This journalwill describe analyze performance in the SPV Purwakarta Factory area, which known asbeing area coverage problems. Place combat in SPV area with BTS Ciseureuh as BTS farend and use the RFS celwafe 90ï° antenna so the performance of signal quality will beappropriate as standard well establishedKeynote: coverage, signal strength, line of sight